Habitual biting of a finger in a child - K N Sarveswari; M Riswana Jasmine; N Mahesh (Indian Journal of Paediatric Dermatology, 2017)
A 3-year-old male child was brought by his parents with a nonhealing ulcer on the right middle finger having no significant history except for an injury sustained to the right elbow in December 2013. On further probing, the mother revealed that the child used to indulge in habitual biting of his right middle finger while watching TV. Initially he was investigated extensively by a vascular surgeon and no abnormality was detected. He was later referred to the dermatology department and on examination, the patient was attentive with normal behaviour. The right upper limb was slightly larger than left. There was no deformity of the right elbow. The right third fingertip was enlarged and mutilated. There was no nerve thickening or hypopigmented patch. There was loss of sensation on the right hand and arm. Differential diagnosis of Lesch–Nyhan syndrome and congenital sensory neuropathy were considered. The patient was referred to a neurologist who investigated further with magnetic resonance imaging (MRI), and the final diagnosis of syringomyelia was made based on MRI findings.